(untitled) (Research, Society and Development, 2020)
The official documents that establish the methodological guidelines for Youth and Adult Education (EJA) prioritize strategies that value the students’ knowledge based on teaching practices permeated by dialogue. Although such guidelines exist, there seems to be a gap between them and what is experienced in schools. Such detachment is evident when faced with teachers frustrated with their practices when they realize that they do not arouse their students’ interest in what they intend to teach. This work arises from a visit by two university professors to a public school to publicize a university extension project. After this first contact, a physics teacher from the college asks for help from university professors to help him make his class more attractive to his EJA class. In this way, a work was carried out between researching professors (universit) and a partner professor in order to clarify the theoretical and methodological assumptions of Science Education in EJA with the approach of Science Education through Research. A class on Refraction of Light was prepared and taught by the partner teacher using materials available at the school and changing the way the class was conducted. To analyze the results, teaching episodes in which the teacher’s and students’ statements are described, were selected in order to highlight the skills recommended in scientific investigation. With the analysis of the results, it is verified that the Teaching of Sciences by Research is feasible in EJA and for that to become a reality, it is necessary to continue training and / or partnerships between universities and teachers from the public education network, so that through research or extension solve together the problems that permeate education.